Chemoperception of Specific Amino Acids Controls Phytopathogenicity in Pseudomonas syringae pv. tomato - Jean Paul Cerna-Vargas (American Society for Microbiology, 2019)
ABSTRACT Chemotaxis has been associated with the pathogenicity of bacteria in plants and was found to facilitate bacterial entry through stomata and wounds. However, knowledge regarding the plant signals involved in this process is scarce. We have addressed this issue using Pseudomonas syringae pv. tomato, which is a foliar pathogen that causes bacterial speck in tomato. We show that the chemoreceptor P. syringae pv. tomato PscA (PsPto-PscA) recognizes specifically and with high affinity l-Asp, l-Glu, and d-Asp. The mutation of the chemoreceptor gene largely reduced chemotaxis to these ligands but also altered cyclic di-GMP (c-di-GMP) levels, biofilm formation, and motility, pointing to cross talk between different chemosensory pathways. Furthermore, the PsPto-PscA mutant strain showed reduced virulence in tomato. Asp and Glu are the most abundant amino acids in plants and in particular in tomato apoplasts, and we hypothesize that this receptor may have evolved to specifically recognize these compounds to facilitate bacterial entry into the plant. Infection assays with the wild-type strain showed that the presence of saturating concentrations of d-Asp also reduced bacterial virulence. IMPORTANCE There is substantive evidence that chemotaxis is a key requisite for efficient pathogenesis in plant pathogens. However, information regarding particular bacterial chemoreceptors and the specific plant signal that they sense is scarce. Our work shows that the phytopathogenic bacterium Pseudomonas syringae pv. tomato mediates not only chemotaxis but also the control of pathogenicity through the perception of the plant abundant amino acids Asp and Glu. We describe the specificity of the perception of l- and d-Asp and l-Glu by the PsPto-PscA chemoreceptor and the involvement of this perception in the regulation of pathogenicity-related traits. Moreover, a saturating concentration of d-Asp reduces bacterial virulence, and we therefore propose that ligand-mediated interference of key chemoreceptors may be an alternative strategy to control virulence.